Molecular Interaction Mapping of Paederia foetida Phytochemicals against NF-kB p65 Highlights Their Potential in Modulating Systemic Inflammation - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Biology, Medicine, & Natural Product Chemistry, 2026)
Systemic inflammation is a fundamental pathological process involved in the development of various chronic diseases, with nuclear factor kappa B (NF-kB) p65 acting as a central transcriptional regulator of inflammatory responses. Paederia foetida L., commonly known as Daun Kentut, has been traditionally used as an anti-inflammatory medicinal plant; however, its molecular mechanisms of action remain poorly understood. This study aimed to investigate the molecular interactions between selected P. foetida phytochemicals and the NF-kB p65 protein using an in silico approach. Molecular docking was performed to evaluate binding affinity and interaction profiles of major phytochemical constituents, including flavonoids, iridoid glycosides, and phenolic acids. The docking results revealed that several compounds exhibited favorable binding energies and stable interaction patterns with key amino acid residues of NF-kB p65, such as Lys221, Arg246, Ser276, and Glu279. Among the tested compounds, quercetin and asperuloside demonstrated strong binding affinity and multiple hydrogen bonds within the transcriptionally active region of NF-kB p65. These interaction profiles were comparable to those of a reference inhibitor. The findings suggest that P. foetida phytochemicals have the potential to modulate NF-?B–mediated inflammatory signaling at the molecular level. This study provides mechanistic support for the traditional use of P. foetida as an anti-inflammatory agent and highlights its potential as a source of natural compounds for the development of inflammation-modulating therapeutics.